Collection of Chigatai Coins in Samarkand State Museum-Reserve - Dalieva, Navbakhor (Researchparks Publishing, 2023)
This article discusses the collection of coins belonging to the Chigatai state, stored in the funds of the Samarkand State Museum-Reserve, its rarity, value, the structure of coins and money, their signs, stamps, weights, the importance of monetary reforms.